How to Develop an Electronic Clinical Endometriosis Research File Integrated in Clinical Practice. (9th July 2015) - Vanhie, A.; Fassbender, A.; O, D.; Tomassetti, C.; Meuleman, C.; Peeraer, K.; Debrock, S.; D'Hooghe, Th.
Abstract : Endometriosis is associated with a range of pelvic-abdominal pain symptoms and infertility. It is a chronic disease that can have a significant impact on various aspects of women's lives, including their social and sexual relationships, work, and study. Despite several international guidelines on the management of endometriosis, there is a wide variety of clinical practice in the management of endometriosis, resulting in many women receiving delayed or suboptimal care. In this paper we discuss the possibilities and benefits of using electronic health records for clinical research in the field of endometriosis. The development of a wide range of clinical software for electronic patient records has made the registration of large datasets feasible and the integration of research files and clinical files possible. Integration of global standards on registration of endometriosis care in electronic health records could improve reporting of research data and facilitate the execution of large, multicentre randomized trials on the management of endometriosis. These highly needed trials could bring us the evidence needed for the optimisation of management of women with endometriosis.